(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
Two species of angiosperms, Spiradiclis bifida Kurz (Rubiaceae) and Strobilanthes urticifolia Wall. ex Kuntze (Acanthaceae ) are being reported as new records for Bangladesh. One species, Corymborkis veratrifolia (Reinw.) Blume belonging to the Orchidaceae has been rediscovered from Hazarikhil Wildlife Sanctuary after about 90 years of last record. These species are described with updated nomenclature, synonyms, taxonomic description, ecology and geographical distribution. Illustrations with field photographs are also provided. Bangladesh J. Plant Taxon. 24(2): 227–231.